Genre-specific Features of the Short Story in Serbian Realism - Stakić, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper will discuss genre-specific features of the short story in Serbian Realism. To establish genre-specific, primarily linguistic and stylistic features of the short story in Serbian Realism and prose in general, we will describe stylistic attributes that connect literary works written in the period of Realism as a movement and determine common stylistic features that link them. In addition, we will also examine the status of the prose text, the creative method of which was defined as realist in contemporary Serbian literature. Conclusions indicate that the structure of the auctorial short story is not subject to strict theoretical rules and that the term realist short story does not restrict the story to the period of the epoch of Realism, but allows it to apply to every literary period in which authors used the objective method to depict events and protagonists.